Barriers and facilitators to provide quality TIA care in the Veterans Healthcare Administration. (12th December 2017) - Damush, Teresa M.; Miech, Edward J.; Sico, Jason J.; Phipps, Michael S.; Arling, Greg; Ferguson, Jared; Austin, Charles; Myers, Laura; Baye, Fitsum; Luckhurst, Cherie; Keating, Ava B.; Moran, Eileen; et al.
Abstract : Objective: To identify key barriers and facilitators to the delivery of guideline-based care of patients with TIA in the national Veterans Health Administration (VHA). Methods: We conducted a cross-sectional, observational study of 70 audiotaped interviews of multidisciplinary clinical staff involved in TIA care at 14 VHA hospitals. We de-identified and analyzed all transcribed interviews. We identified emergent themes and patterns of barriers to providing TIA care and of facilitators applied to overcome these barriers. Results: Identified barriers to providing timely acute and follow-up TIA care included difficulties accessing brain imaging, a constantly rotating pool of housestaff, lack of care coordination, resource constraints, and inadequate staff education. Key informants revealed that both stroke nurse coordinators and system-level factors facilitated the provision of TIA care. Few facilities had specific TIA protocols. However, stroke nurse coordinators often expanded upon their role to include TIA. They facilitated TIA care by (1) coordinating patient care across services, communicating across service lines, and educating clinical staff about facility policies and evidence-based practices; (2) tracking individual patients from emergency departments to inpatient settings and to discharge for timely follow-up care; (3) providing and referring TIA patients to risk factor management programs; and (4) performing regular audit and feedback of quality performance data. System-level facilitators included clinical service leadership engagement and use of electronic tools for continuous care across services. Conclusions: The local organization within a health care facility may be targeted to cultivate internal facilitators and a systemic infrastructure to provide evidence-based TIA care.